Design of a Dynamic Simulator for a Biped Robot. (4th May 2021) - Bravo M, Diego A.; Rengifo Rodas, Carlos F.
Abstract : Simulation is a virtual representation of a dynamic system. For the case of mechanical systems, the simulator is used to calculate the reaction forces between its base and the ground and other constraints. The intermittent nature of these forces and the mathematical inequalities that they must satisfy lead to models described by hybrid algebraic differential equations. In this paper, a simulator was developed for a seven degrees of freedom planar biped robot, which was modeled using the Euler-Lagrange formulation. This model allowed the design and implementation of a control strategy for balance management, and the monitoring of articular reference paths are tested in the simulator before proceeding to implementation on the actual prototype.